Navigating the green transition: a comparative analysis of green building policy frameworks in China, the EU, and the US using structural topic modeling - Cai, Jingwen; Xie, Yingchong; Yin, Yifen; Hu, Haoqian; Wang, Chunning (Frontiers in Built Environment, 2025)
Against the backdrop of escalating global climate change challenges, the green transition of the building sector has emerged as a core agenda. However, how the distinct governance models of major economies shape unique policy paths and whether these paths are converging over the long term remains underexplored through systematic, data-driven empirical research. To fill this gap, this study employs the structural topic model method for a quantitative analysis of 206 national-level green building policy documents issued by China, the European Union, and the United States from 2000 to 2024. Our analysis reveals three distinct policy pathways. China employs a planning-driven model focused on national goals and technical standards. The EU utilizes a supranational, regulatory integration model centered on legally binding directives and nearly zero-energy building targets. In contrast, the US follows a market-incentive federalist model dominated by financial instruments like tax credits and subsidies. Despite these divergent approaches, we find emerging convergence on two key tools: building energy codes and residential subsidies. This study contributes a data-driven, dynamic framework for comparative policy analysis, revealing strategic divergences and convergences among key global actors. The findings offer empirical insights for policy design, cross-national learning, and international cooperation in accelerating green building transition.